Prenatal IV Cocaine: Alterations in Auditory Information Processing - Mactutus, Charles F.; Harrod, Steven B.; Hord, Lauren L.; Moran, Landhing M.; Booze, Rosemarie M. (Frontiers in Psychiatry, 2011)
One clue regarding the basis of cocaine-induced deficits in attentional processing is provided by the clinical findings of changes in the infants’ startle response; observations buttressed by neurophysiological evidence of alterations in brainstem transmission time. Using the IV route of administration and doses that mimic the peak arterial levels of cocaine use in humans, the present study examined the effects of prenatal cocaine on auditory information processing via tests of the acoustic startle response (ASR), habituation, and prepulse inhibition (PPI) in the offspring. Nulliparous Long-Evans female rats, implanted with an IV access port prior to breeding, were administered saline, 0.5, 1.0, or 3.0 mg/kg/injection of cocaine HCL (COC) from gestation day (GD)8-20 (1x/day-GD8-14, 2x/day-GD15-20). COC had no significant effects on maternal/litter parameters or growth of the offspring. At 18-20 days of age, one male and one female, randomly selected from each litter displayed an increased ASR (>30% for males at 1.0 mg/kg and >30% for females at 3.0 mg/kg). When reassessed in adulthood (D90-100), a linear dose-response increase was noted on response amplitude. At both test ages, within-session habituation was retarded by prenatal cocaine treatment. Testing the females in diestrus vs. estrus did not alter the results. Prenatal cocaine altered the PPI response function across interstimulus interval (ISI) and induced significant sex-dependent changes in response latency. Idazoxan, an alpha2-adrenergic receptor antagonist, significantly enhanced the ASR, but less enhancement was noted with increasing doses of prenatal cocaine. Thus, in utero exposure to cocaine, when delivered via a protocol designed to capture prominent features of recreational usage, causes persistent, if not permanent, alterations in auditory information processing, and suggests dysfunction of the central noradrenergic circuitry modulating, if not mediating, these responses.